Low-brittleness carbon fiber composite material and preparation method thereof

By using a combination of vinyl ester resin, polyamide, polycarbonate and carbon fiber in the badminton racket material and covering the transition layer on the carbon fiber surface, the problem of insufficient brittleness of existing materials is solved, and tensile, bending and impact resistance is improved Strength, suitable for the production of high-performance badminton rackets.

CN119264607AInactive Publication Date: 2025-01-07JIANGSU ZHENGHE SPORTS GOODS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411400465.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing badminton racket materials have high brittleness, resulting in insufficient tensile strength, bending strength and impact strength, which cannot meet the demand for material performance in modern badminton sports.

Method used

Using low-brittle carbon fiber composite material, composed of vinyl ester resin, polyamide, polycarbonate and carbon fiber, and covered with transition layers on the surface of the carbon fiber, it is prepared by oxidative modification and heating and pressurization to enhance the interface bonding and resistance of the material. Impact performance.

Benefits of technology

The prepared low-brittle carbon fiber composite material has high tensile strength, bending strength and impact strength, and is less brittle, and is suitable for the production of high-performance badminton rackets and other sports equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075134010000061
    Figure BDA0005075134010000061
  • Figure BDA0005075134010000071
    Figure BDA0005075134010000071
Patent Text Reader

Abstract

The invention relates to the field of preparation of carbon fiber composite materials, in particular to a low-brittleness carbon fiber composite material and a preparation method thereof. The invention provides a low-brittleness carbon fiber composite material. The low-brittleness carbon fiber composite material is prepared from vinyl ester resin; a polyamide; a polycarbonate; carbon fibers; a coupling agent; a curing agent; wherein the coupling agent is isoquinolone. The preparation method of the low-brittleness carbon fiber composite material comprises the following steps: S1, carbon fiber modification; s2, preparing a transition layer; s3, preparing the low-brittleness carbon fiber composite material. The transition layer is added to better combine the carbon fiber layer and the resin matrix, enhance the interface combination of the composite material, improve the interface performance, enhance the interface shear strength and reduce the brittleness of the composite material so as to adapt to stronger impact force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of carbon fiber composite materials, and in particular to a low-brittle carbon fiber composite material and a preparation method thereof. Background Art

[0002] Badminton is a sport with a long history. It has the characteristics of low threshold, low sports injury, high fun and high training effect. It can not only exercise the body, improve cardiopulmonary function and coordination ability, but also enhance people's psychological quality and team spirit. With the improvement of people's health awareness and the popularization of the concept of national fitness, badminton has developed into a popular national fitness sport.

[0003] As one of the core equipments of badminton, the performance and quality of badminton rackets play a vital role in the performance of athletes. A good badminton racket can help athletes better control the ball path, increase the speed and power of hitting the ball, and reduce physical exertion and the risk of injury. Therefore, in modern badminton, the selection and use of badminton rackets are increasingly valued by athletes and coaches.

[0004] The strength and wear resistance of the materials used to make a badminton racket will determine the quality of the racket; and the strength and wear resistance of badminton racket materials are closely related to the brittleness of the material. Therefore, the invention of a low-brittleness carbon fiber composite material has a very broad development prospect. Summary of the invention

[0005] In view of the above-mentioned existing technical problems, a low-brittle carbon fiber composite material and a preparation method thereof are provided. The carbon fiber composite material prepared by this method has high tensile strength, high bending strength, strong impact strength and low brittleness, and is very suitable for the production of sports equipment such as badminton rackets.

[0006] The present invention discloses a low-brittle carbon fiber composite material, which is composed of the following components in parts by weight:

[0007] 35-55 parts of vinyl ester resin; 18-30 parts of polyamide; 13-18 parts of polycarbonate; 32-37 parts of carbon fiber; 1-6 parts of coupling agent; 1-2 parts of curing agent.

[0008] Preferably, the coupling agent is an isoquinolone.

[0009] Preferably, the heat stabilizer is composed of polyurea and pentaerythritol bismaleate in a mass ratio of 1:(1.3-1.5).

[0010] The present invention also discloses a method for preparing a low-brittle carbon fiber composite material, comprising the following steps:

[0011] S1 carbon fiber modification: add carbon fiber to a reactor, then add an oxidant to the container to immerse the carbon fiber, heat it up to cause an oxidation reaction, filter it after the reaction is completed, collect the filter cake, and dry the filter cake to obtain modified carbon fiber;

[0012] S2 transition layer preparation: adding the coupling agent to anhydrous methanol, stirring and dissolving them, and preparing a transition layer liquid, then placing the modified carbon fiber obtained in step S1 on a coating plate, spraying the transition layer liquid evenly on the surface of the modified carbon fiber, and then drying to obtain a modified carbon fiber coated with a transition layer;

[0013] S3 Preparation of low-brittle carbon fiber composite materials: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, and then heat and pressurize it to solidify it to form a low-brittle carbon fiber composite material.

[0014] Preferably, in the S1 carbon fiber modification step, the oxidant is a hydrogen peroxide solution with a mass fraction of 30 to 40%.

[0015] Preferably, the temperature of the oxidation reaction in the S1 carbon fiber modification step is 100-150°C.

[0016] Preferably, the duration of the oxidation reaction in the S1 carbon fiber modification step is 0.5 to 2.5 hours.

[0017] Preferably, the drying temperature in the S1 carbon fiber modification step is 50-75°C.

[0018] Preferably, in the S2 transition layer preparation step, the mass ratio of the coupling agent to anhydrous methanol is 1:(3-6).

[0019] Preferably, in the S3 low-brittle carbon fiber composite material preparation step, the mass ratio of vinyl ester resin to anhydrous methanol is 1:(15-20).

[0020] Preferably, in the S3 low-brittle carbon fiber composite material preparation step, the heating temperature is 95-120° C.; the pressurization pressure is 1.5-2 MPa; and the curing time is 2-3 h.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention provides a low-brittle carbon fiber composite material. The raw materials are composed of carbon fiber and a resin matrix, wherein the resin matrix is ​​composed of vinyl ester resin, polyurethane and polycarbonate. After the carbon fiber is oxidatively modified, a transition layer is covered on the surface thereof. The transition layer is formed by combining coupling agent isoquinolone with methanol. The reason for adding the transition layer is that the interface bonding of the composite material can be enhanced, the interface performance can be improved, the interface shear strength can be enhanced, the brittleness of the composite material can be reduced, and the composite material can adapt to stronger impact force. DETAILED DESCRIPTION

[0023] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0024] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0025] Embodiment 1: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0026] 35 parts of vinyl ester resin, 18 parts of polyamide, 13 parts of polycarbonate, 32 parts of carbon fiber, 1 part of coupling agent, and 1 part of curing agent, wherein the coupling agent is isoquinolone.

[0027] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0028] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add 30% by mass hydrogen peroxide solution to the container, immerse the carbon fiber, raise the temperature to 100°C for oxidation reaction, the oxidation reaction time is 0.5h, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 50°C, after drying, obtain modified carbon fiber.

[0029] Preparation of S2 transition layer: Add coupling agent isoquinolone to anhydrous methanol, the mass ratio of coupling agent isoquinolone to anhydrous methanol is 1:3, stir to dissolve each other, and prepare a transition layer liquid, then place the modified carbon fiber obtained in step S1 on the coating plate, spray the transition layer liquid evenly on the surface of the modified carbon fiber, and then obtain the modified carbon fiber coated with a transition layer after drying.

[0030] Preparation of S3 low-brittle carbon fiber composite material: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, with the mass ratio of vinyl ester resin to anhydrous methanol being 1:15, to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, then heat to 95°C, pressurize at 1.5MPa, and cure for 3h, to form a low-brittle carbon fiber composite material after curing.

[0031] Embodiment 2: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0032] 38 parts of vinyl ester resin, 21 parts of polyamide, 14 parts of polycarbonate, 33 parts of carbon fiber, 2 parts of coupling agent, and 1.2 parts of curing agent, wherein the coupling agent is isoquinolone.

[0033] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0034] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add a 32% by mass hydrogen peroxide solution into the container, immerse the carbon fiber, raise the temperature to 110°C for oxidation reaction, the oxidation reaction time is 0.7h, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 55°C, after drying, obtain modified carbon fiber.

[0035] Preparation of S2 transition layer: Add coupling agent isoquinolone to anhydrous methanol, the mass ratio of coupling agent isoquinolone to anhydrous methanol is 1:3.5, stir to dissolve each other, and prepare a transition layer liquid, then place the modified carbon fiber obtained in step S1 on the coating plate, spray the transition layer liquid evenly on the surface of the modified carbon fiber, and then obtain the modified carbon fiber coated with a transition layer after drying.

[0036] Preparation of S3 low-brittle carbon fiber composite material: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, with the mass ratio of vinyl ester resin to anhydrous methanol being 1:16, to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, then heat to 100°C, pressurize at 1.6MPa, and cure for 2.8h, to form a low-brittle carbon fiber composite material after curing.

[0037] Embodiment 3: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0038] 43 parts of vinyl ester resin, 24 parts of polyamide, 15 parts of polycarbonate, 34 parts of carbon fiber, 3 parts of coupling agent, and 1.4 parts of curing agent, wherein the coupling agent is isoquinolone.

[0039] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0040] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add a 34% mass fraction hydrogen peroxide solution into the container, immerse the carbon fiber, raise the temperature to 120°C for oxidation reaction, the oxidation reaction time is 1.1h, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 60°C, after drying, obtain modified carbon fiber.

[0041] Preparation of S2 transition layer: Add coupling agent isoquinolone to anhydrous methanol, the mass ratio of coupling agent isoquinolone to anhydrous methanol is 1:4, stir to dissolve each other, and prepare a transition layer liquid, then place the modified carbon fiber obtained in step S1 on the coating plate, spray the transition layer liquid evenly on the surface of the modified carbon fiber, and then obtain the modified carbon fiber coated with a transition layer after drying.

[0042] Preparation of S3 low-brittle carbon fiber composite material: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, the mass ratio of vinyl ester resin to anhydrous methanol is 1:17, and obtain resin slurry; spread the modified carbon fiber coated with transition layer obtained in S2 in the mold, add the resin slurry into the mold, and then heat to 105°C, pressurize to 1.7MPa, and cure for 2.6h. After the curing is completed, a low-brittle carbon fiber composite material is formed.

[0043] Embodiment 4: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0044] 47 parts of vinyl ester resin, 26 parts of polyamide, 16 parts of polycarbonate, 35 parts of carbon fiber, 4 parts of coupling agent, and 1.6 parts of curing agent, wherein the coupling agent is isoquinolone.

[0045] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0046] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add a 36% mass fraction hydrogen peroxide solution into the container, immerse the carbon fiber, raise the temperature to 130°C for oxidation reaction, the oxidation reaction time is 1.6 hours, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 65°C, after drying, obtain modified carbon fiber.

[0047] Preparation of S2 transition layer: Add coupling agent isoquinolone to anhydrous methanol, the mass ratio of coupling agent isoquinolone to anhydrous methanol is 1:4.5, stir to dissolve each other, and prepare a transition layer liquid, then place the modified carbon fiber obtained in step S1 on the coating plate, spray the transition layer liquid evenly on the surface of the modified carbon fiber, and then obtain the modified carbon fiber coated with a transition layer after drying.

[0048] Preparation of S3 low-brittle carbon fiber composite material: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, with the mass ratio of vinyl ester resin to anhydrous methanol being 1:18, to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, and then heat to 110°C, pressurize at 1.8MPa, and cure for 2.4h, to form a low-brittle carbon fiber composite material after the curing is completed.

[0049] Embodiment 5: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0050] 51 parts of vinyl ester resin, 28 parts of polyamide, 17 parts of polycarbonate, 36 parts of carbon fiber, 5 parts of coupling agent, and 1.8 parts of curing agent, wherein the coupling agent is isoquinolone.

[0051] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0052] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add a 38% by mass hydrogen peroxide solution into the container, immerse the carbon fiber, raise the temperature to 140°C for oxidation reaction, the oxidation reaction time is 1.8 hours, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 70°C, after drying, obtain modified carbon fiber.

[0053] Preparation of S2 transition layer: Add coupling agent isoquinolone to anhydrous methanol, the mass ratio of coupling agent isoquinolone to anhydrous methanol is 1:5, stir to dissolve each other, and prepare a transition layer liquid, then place the modified carbon fiber obtained in step S1 on the coating plate, spray the transition layer liquid evenly on the surface of the modified carbon fiber, and then obtain the modified carbon fiber coated with a transition layer after drying.

[0054] Preparation of S3 low-brittle carbon fiber composite material: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, the mass ratio of vinyl ester resin to anhydrous methanol is 1:19, to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, and then heat to 115°C, pressurize to 1.9MPa, and cure for 2.4h, to form a low-brittle carbon fiber composite material after curing.

[0055] Embodiment 6: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0056] 55 parts of vinyl ester resin, 30 parts of polyamide, 18 parts of polycarbonate, 37 parts of carbon fiber, 6 parts of coupling agent, and 2 parts of curing agent, wherein the coupling agent is isoquinolone.

[0057] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0058] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add 40% hydrogen peroxide solution by mass into the container, immerse the carbon fiber, raise the temperature to 150°C for oxidation reaction, the oxidation reaction time is 40 hours, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 75°C, after drying, obtain modified carbon fiber.

[0059] Preparation of S2 transition layer: Add coupling agent isoquinolone to anhydrous methanol, the mass ratio of coupling agent isoquinolone to anhydrous methanol is 1:5, stir to dissolve each other, and prepare a transition layer liquid, then place the modified carbon fiber obtained in step S1 on the coating plate, spray the transition layer liquid evenly on the surface of the modified carbon fiber, and then obtain the modified carbon fiber coated with a transition layer after drying.

[0060] Preparation of S3 low-brittle carbon fiber composite material: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, with the mass ratio of vinyl ester resin to anhydrous methanol being 1:20, to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, then heat to 120°C, pressurize to 2.0MPa, and cure for 2.0h, to form a low-brittle carbon fiber composite material after curing.

[0061] Comparative Example 1: A low-brittle carbon fiber composite material, comprising the following components in parts by weight:

[0062] 51 parts of vinyl ester resin; 28 parts of polyamide; 17 parts of polycarbonate; 36 parts of carbon fiber; 1.8 parts of curing agent.

[0063] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0064] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add a 38% by mass hydrogen peroxide solution into the container, immerse the carbon fiber, raise the temperature to 140°C for oxidation reaction, the oxidation reaction time is 1.8 hours, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 70°C, after drying, obtain modified carbon fiber.

[0065] Preparation of S2 low-brittle carbon fiber composite materials: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn, with the mass ratio of vinyl ester resin to anhydrous methanol being 1:19, to obtain resin slurry; spread the modified carbon fiber obtained in S1 in a mold, add the resin slurry into the mold, then heat to 115°C, pressurize to 1.9 MPa, and cure for 2.4 hours. After the curing is completed, a low-brittle carbon fiber composite material is formed.

[0066] Comparative Example 2: A low-brittle carbon fiber composite material, consisting of the following components in parts by weight:

[0067] 51 parts of vinyl ester resin, 28 parts of polyamide, 17 parts of polycarbonate, 36 parts of carbon fiber, 5 parts of coupling agent, and 1.8 parts of curing agent, wherein the coupling agent is isoquinolone.

[0068] A method for preparing a low-brittle carbon fiber composite material comprises the following steps:

[0069] S1 Carbon fiber modification: Add carbon fiber to the reactor, then add a 38% by mass hydrogen peroxide solution into the container, immerse the carbon fiber, raise the temperature to 140°C for oxidation reaction, the oxidation reaction time is 1.8 hours, after the reaction is completed, filter and collect the filter cake, then take out the filter cake and dry it at 70°C, after drying, obtain modified carbon fiber.

[0070] Preparation of S2 low-brittle carbon fiber composite materials: dissolve vinyl ester resin, polyamide, polycarbonate, coupling agent and curing agent in anhydrous methanol in turn, with the mass ratio of vinyl ester resin to anhydrous methanol being 1:19, to obtain resin slurry; spread the modified carbon fiber obtained in S1 in a mold, add the resin slurry into the mold, then heat to 115°C, pressurize at 1.9 MPa, and cure for 2.4 hours to form a low-brittle carbon fiber composite material after curing.

[0071] The carbon fiber composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were tested for performance, and the test results are shown in the following table:

[0072]

[0073]

[0074] Examples 1 to 6 have different raw material ratios and different preparation conditions during the preparation process, resulting in slightly different properties of the carbon fiber composite materials obtained. As can be seen from the above table, in Examples 4 to 6, various properties tend to be stable, indicating that the obtained carbon fiber composite materials have high density, high tensile strength, high bending strength, strong impact strength, and low brittleness. Among them, the raw material ratio and experimental conditions of Example 5 are the best.

[0075] In Comparative Example 1, no coupling agent is added to the raw materials, and therefore there is no step of preparing the S2 transition layer in the preparation method, and the modified carbon fiber is directly contacted and extruded with the resin matrix to form a carbon fiber composite material; in Comparative Example 2, a coupling agent is added to the raw materials, but in the preparation method, the coupling agent is not prepared into a transition layer, but is directly added to the preparation of the resin matrix and combined with the modified carbon fiber to form a carbon fiber composite material.

[0076] Comparing the test results of Comparative Examples 1 to 2 with the test results of Example 5, it can be seen that the properties of the carbon fiber composite materials obtained in Comparative Examples 1 and 2 are worse than those in Example 5. This shows that the addition of a coupling agent is necessary to reduce the resistance of the carbon fiber composite material and enhance the impact stress resistance. This is because the coupling agent added in the present invention is isoquinolone, which contains naphthyl and hydroxyl groups and is a condensed ring compound. It takes π-π bond stacking as the dominant force to form molecular self-assembly on the surface of the carbon fiber to form a collar-like nanostructure; the graphite-like sp 2 The hybrid structure can form a strong π-π bond interaction with the condensed ring molecules; polyamide is selected as a part of the resin matrix component, and the amino group therein forms a strong hydrogen bond with the hydroxyl group in the transition layer, which further enhances the bonding between the resin matrix and the modified carbon fiber, realizes the interface phase stiffness enhancement, and synergizes the wettability, chemical bonding and mechanical interlocking between the modified carbon fiber and the resin matrix.

[0077] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A low-brittle carbon fiber composite material, characterized in that: It is composed of the following ingredients in parts by weight: 35-55 parts of vinyl ester resin; 18-30 parts of polyamide; 13-18 parts of polycarbonate; 32-37 parts of carbon fiber; 1-6 parts of coupling agent; 1-2 parts of curing agent.

2. A low-brittle carbon fiber composite material according to claim 1, characterized in that: The coupling agent is isoquinolone.

3. A method for preparing a low-brittle carbon fiber composite material, characterized in that: The following steps are involved: S1 carbon fiber modification: adding carbon fiber to a reactor, then adding an oxidant to the reactor to immerse the carbon fiber, heating to cause an oxidation reaction, and obtaining a reaction liquid after the reaction is completed. The reaction liquid is filtered, the filter cake is collected, and the filter cake is dried to obtain modified carbon fiber; S2 transition layer preparation: adding the coupling agent to anhydrous methanol, stirring and dissolving them, and preparing a transition layer liquid, then placing the modified carbon fiber obtained in step S1 on a coating plate, spraying the transition layer liquid evenly on the surface of the modified carbon fiber, and then drying to obtain a modified carbon fiber coated with a transition layer; S3 Preparation of low-brittle carbon fiber composite materials: dissolve vinyl ester resin, polyamide, polycarbonate and curing agent in anhydrous methanol in turn to obtain resin slurry; spread the modified carbon fiber coated with a transition layer obtained in S2 in a mold, add the resin slurry into the mold, and then heat and pressurize it to solidify it to form a low-brittle carbon fiber composite material.

4. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: In the S1 carbon fiber modification step, the oxidant is a hydrogen peroxide solution with a mass fraction of 30 to 40%.

5. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: The temperature of the oxidation reaction in the S1 carbon fiber modification step is 100-150°C.

6. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: The duration of the oxidation reaction in the S1 carbon fiber modification step is 0.5 to 2.5 hours.

7. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: In the S1 carbon fiber modification step, the drying temperature is 50-75°C.

8. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: In the S2 transition layer preparation step, the mass ratio of the coupling agent to anhydrous methanol is 1:(3-6).

9. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: In the S3 low-brittle carbon fiber composite material preparation step, the mass ratio of vinyl ester resin to anhydrous methanol is 1:(15-20).

10. The method for preparing a low-brittle carbon fiber composite material according to claim 3, characterized in that: In the preparation steps of the S3 low-brittle carbon fiber composite material, the heating temperature is 95-120°C; the pressurization pressure is 1.5-2MPa; and the curing time is 2-3h.